2008
DOI: 10.1016/j.ceb.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Cdk-counteracting phosphatases unlock mitotic exit

Abstract: Entry into mitosis of the eukaryotic cell cycle is driven by rising cyclin-dependent kinase (Cdk) activity. During exit from mitosis, Cdk activity must again decline. Cdk downregulation by itself, however, is not able to guide mitotic exit, if not a phosphatase reverses mitotic Cdk phosphorylation events. In budding yeast, this role is played by the Cdc14 phosphatase. We are gaining an increasingly detailed picture of its regulation during anaphase, and of the way it orchestrates ordered progression through mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
120
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 67 publications
(53 reference statements)
0
120
0
Order By: Relevance
“…While fission yeast and C. elegans also rely to some extent on Cdc14 homologues, 68-72 the majority of eukaryotes do not need Cdc14 for mitotic exit. 73,74 A systematic RNAi screen in Drosophila S2 cells revealed that several phosphatases are required to progress through and exit mitosis. 75 In Xenopus egg extracts PP1, PP2A and calcineurin have been shown to oppose the Cdk1 activity.…”
Section: Regulation Of Chromosome Segregation In Anaphasementioning
confidence: 99%
“…While fission yeast and C. elegans also rely to some extent on Cdc14 homologues, 68-72 the majority of eukaryotes do not need Cdc14 for mitotic exit. 73,74 A systematic RNAi screen in Drosophila S2 cells revealed that several phosphatases are required to progress through and exit mitosis. 75 In Xenopus egg extracts PP1, PP2A and calcineurin have been shown to oppose the Cdk1 activity.…”
Section: Regulation Of Chromosome Segregation In Anaphasementioning
confidence: 99%
“…In Caenorhabditis elegans, depletion of CeCDC-14 by RNAi causes defects in cytokinesis; however, this is most likely due to failure to form an intact central spindle (Gruneberg et al, 2002). The human genome encodes two Cdcl4 homologues, Cdc14A and Cdc14B and both can rescue Cdc14 yeast phenotypes (Queralt and Uhlmann, 2008), suggesting functional conservation. However, neither Cdc14A nor Cdc14B are required for mitotic exit in higher eukaryotes (Berdougo et al, 2008) although they do seem to be required to generally dephosphorylate Cdk targets (Mocciaro and Schiebel, 2010).…”
Section: Mitotic Phosphatases In Mammalian Cellsmentioning
confidence: 99%
“…Thus the action of Cdc14 is, in part, to counteract Cdk activity by dephosphorylating Cdk substrates (Visintin et al, 1998). Cdc14 is tightly regulated both spatially and temporally Amon, 2004, Queralt andUhlmann, 2008) as well as being a part of several feedback loops that contribute to a rapid metaphase-anaphase transition (Holt et al, 2008). We have gained a detailed molecular picture of the way that the Cdc14 phosphatase orchestrates mitotic exit in yeast (reviewed in Amon, 2004, Queralt andUhlmann, 2008)).…”
Section: Mitotic Phosphatases In Mammalian Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Named for Cdc14, the founding member identified in the budding yeast, Saccharomyces cerevisiae, these phosphatases reverse Cdk-mediated phosphorylation events to promote mitotic exit and cytokinesis (Queralt and Uhlmann, 2008). Like other Cdc14 family members, the S. pombe Cdc14 homologue, Clp1/Flp1, also functions in these processes.…”
Section: Introductionmentioning
confidence: 99%